Spiraal '68. - Patteeuw, Roland; Stadhuis Roeselare (Roeselare : Kulturele Kring De Mandel, 1968)
Claus, Luk ; Decock, Gilbert ; De Keyser, Raoul ; Deneckere, Willem ; Elias, Etienne ; Lagae, Werner ; Raveel, Roger ; Spilliaert, Pol ; Vanallemeersch, Geert ; Van Gysegem, Paul ; VanLierde, Nadine ; Van Severen, Dan
Spiraal '68, Stadhuis Roeselare, 16 maart - 3 april 1968
boek